K2-232 b: a transiting warm Saturn on an eccentric P = 11.2 d orbit around a V = 9.9 star. Issue 2 (27th March 2018) - Brahm, R; Espinoza, N; Jordán, A; Rojas, F; Sarkis, P; Díaz, M R; Rabus, M; Drass, H; Lachaume, R; Soto, M G; Jenkins, J S; Jones, M I; et al.
Abstract: We report the discovery of K2-232 b using photometric data of the Kepler K 2 satellite coupled with ground-based spectroscopic observations. K2-232 b has a mass of M P = 0.397 ± 0.037 M J, a radius of R P = 1.00 ± 0.020 R J, and a moderately low equilibrium temperature of T eq = 1030 ± 15 K due to its relatively large star–planet separation of a = 0.1036 au. K2-232 b orbits its bright ( V = 9.9) late F-type host star in an eccentric orbit ( e = 0.258 ± 0.025) every 11.2 d, and is one of only four well-characterized warm Jupiters having host stars brighter than V = 10. We estimate a heavy element content of 20 ± 7 M⊕ for K2-232 b, which is consistent with standard models of giant planet formation. The bright host star of K2-232 b makes this system a well-suited target for detailed follow-up observations that will aid in the study of the atmospheres and orbital evolution of giant planets at moderate separations from their host stars.